2023
DOI: 10.1002/cam4.5926
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of disease progression during treatment with Osimertinib in patients with EGFR T790M‐positive non‐small cell lung cancer

Abstract: Background: Patterns of treatment failure and subsequent treatment in nonsmall cell lung cancer (NSCLC) patients treated with osimertinib are scarcely known. We analyzed the disease progression during osimertinib treatment to identify potential treatment strategies. Methods:We identified advanced NSCLC patients who commenced osimertinib treatment after progression on previous epidermal growth factor receptor (EGFR)-tyrosine-kinase inhibitor (TKI) from June 2014 to November 2018 from electronic records. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A total of 222 patients were selected from ten articles 13–15,26–32 . Of these 222 patients, 121 patients exhibited the loss of the T790M mutation subsequent to the emergence of resistance to Osimertinib (T790M‐loss group) and 101 patients maintained the T790M mutation (T790M‐maintenance group) while developing resistance to Osimertinib.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 222 patients were selected from ten articles 13–15,26–32 . Of these 222 patients, 121 patients exhibited the loss of the T790M mutation subsequent to the emergence of resistance to Osimertinib (T790M‐loss group) and 101 patients maintained the T790M mutation (T790M‐maintenance group) while developing resistance to Osimertinib.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 222 patients were selected from ten articles. 13 , 14 , 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 Of these 222 patients, 121 patients exhibited the loss of the T790M mutation subsequent to the emergence of resistance to Osimertinib (T790M‐loss group) and 101 patients maintained the T790M mutation (T790M‐maintenance group) while developing resistance to Osimertinib. Pooled analysis showed that the risk value for the T790M‐maintenance group was lower than for the T790M‐loss group (HR: 0.44, 95% CI: 0.30–0.66; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations